Targeted RNA sequencing of adrenal zones using immunohistochemistry-guided capture of formalin-fixed paraffin-embedded tissue. (15th June 2021) - Baker, Jessica E.; Plaska, Samuel W.; Qin, Zhaoping; Liu, Chia-Jen; Rege, Juilee; Rainey, William E.; Udager, Aaron M.
Abstract: Adequate access to fresh or frozen normal adrenal tissue has been a primary limitation to the enhanced characterization of the adrenal zones via RNA sequencing (RNAseq). Herein, we describe the application of targeted RNAseq to formalin-fixed paraffin-embedded (FFPE) normal adrenal gland specimens. Immunohistochemistry (IHC) was used to visualize and guide the capture of the adrenocortical zones and medulla. Following IHC-based tissue capture and isolation of RNA, high-throughput targeted RNAseq highlighted clear transcriptomic differences and identified differentially expressed genes among the adrenal zones. Our data demonstrate the ability to capture FFPE adrenal zone tissue for targeted transcriptomic analyses. Future comparison of normal adrenal zones will improve our understanding of transcriptomic patterns and help identify potential novel pathways controlling zone-specific steroid production. Highlights: IHC-guided capture of FFPE tissue accurately isolates adrenal zones. Targeted RNA sequencing facilitates differentiation of adrenal zones. Adrenal zone transcriptomic analysis highlights molecular pathways and markers.